Identifying the psychological challenges of mothers with a chronically ill child: A phenomenological study - Mahboobeh Rezaei; anahita khodabakhshi-koolaee; Mohammad Reza falsafinejad; Akram Sanagoo (Kerman University of Medical Sciences, 2020)
Introduction: Having a child with a chronic mental illness puts a lot of psychological pressure on family members, especially the mother who takes care of the child. Therefore, this study aimed to identify the psychological challenges of mothers of children with chronic diseases in Karaj. Methods: This study employed a descriptive phenomenological approach using a purposive sampling method and was conducted in 2017. The data were collected through semi-structured interviews with the participants who were mothers of children with a chronic mental illness at the Rehabilitation, Treatment, and Care Center for Neurological and Psychiatric Patients in Mehrafarin, Karaj, of whom 17 were selected to take the interviews. The collected data were analyzed using Colaizzi's seven-step method for data analysis. Results: The results of the study showed that the psychological challenges faced by mothers with chronically ill children can be divided into five main categories: Feeling uncomfortable at home, feeling of constant fear, mental fatigue caused by continuous maternal care, social stigma and restricted interactions, and insufficient financial and support resources. Conclusion: Mothers who have to care for a child with a chronic mental illness are exposed to substantial burden of care and psychological pressure. Some of these psychological challenges are rooted in individual and family issues, and others are rooted in social conditions and seeking support for the patient. Therefore, it seems that the teaching of psychological interventions to mothers should be individually and socially oriented to reduce the psychological challenges and pressures tolerated by mothers with chronically ill children. Of course, concerning objective burden and seeking support, benefiting from insurance and other health services can reduce the problems faced by these mothers.